Quantum dot THz detectors and its applications for imaging - Ikushima, Kenji (SPIE, 2018)
Single photon detection is realized by utilizing semiconductor quantum structures in a wide range of the terahertz (THz) region. In this paper, we review quantum-dot type THz photon detectors and its applications for passive THz imaging.